El desarrollo de los componentes del modelo de prevención para sujetos no obligados: de acuerdo a la Ley 30424 - Atahuamán Páucar, Jhuliana (2018)
The following article addresses Law 304214, the Law that regulates the administrative responsibility of legal entities, including the obligated and the non-obligated subjects by the law, its components and crime prevention models. In order to explain them, the author presents national and international legal instruments such as the Peruvian Technical Regulation NTP-ISO 37001:2017 regarding anti-bribery management systems, the Anti-corruption of Ethics and Compliance Program for Companies issued by the United Nations Office against drugs and crime and the Law 304214 regulation bill.